Resilience, health, and quality of life among long‐term survivors of hematopoietic cell transplantation. Issue 23 (19th August 2015) - Rosenberg, Abby R.; Syrjala, Karen L.; Martin, Paul J.; Flowers, Mary E.; Carpenter, Paul A.; Salit, Rachel B.; Baker, K. Scott; Lee, Stephanie J.
Abstract : BACKGROUND: Low patient‐reported resilience is associated with an ongoing risk of poor health and psychosocial outcomes. Using a large cross‐sectional sample of survivors of hematopoietic cell transplantation (HCT), this study explored associations between patient‐reported resilience, psychological distress, posttraumatic growth, and health‐related quality of life. METHODS: Between July 1, 2013 and June 30, 2014, the annual Fred Hutchinson Cancer Research Center (FHCRC) posttransplant survivorship survey queried patient‐reported health and functional status and included instruments assessing psychosocial outcomes: the 10‐item Connor‐Davidson Resilience Scale, the Posttraumatic Growth Inventory, the Cancer and Treatment Distress measure, and the 12‐item Medical Outcomes Study Short Form quality‐of‐life scale. Multivariate linear and logistic regression models included demographic and health covariates extracted from the FHCRC research database. RESULTS: Among 4643 adult survivors of HCT, 1823 (39%) responded after a single mailing and subsequent reminder letter. The participants' median age was 59 years (interquartile range [IQR], 50‐66 years); 52.5% were male, and most were non‐Hispanic white. The median time since HCT was 9 years (IQR, 3‐18 years). Lower patient‐reported resilience was associated with chronic graft‐versus‐host disease of higher severity, lower performance scores, missing work because of health, and permanent disability (all P  < .0001). After adjustments for demographic and health characteristics, patients reporting low resilience scores had higher odds of having psychological distress (odds ratio [OR], 3.0; 95% confidence interval [CI], 2.1‐4.3) and being in the lowest quartile for mental health–related quality of life (OR, 5.9; 95% CI, 4.4‐8.0). CONCLUSIONS: Patient‐reported resilience is independently associated with health and psychosocial outcomes. Future studies must determine whether interventions can bolster resilience and improve survivorship outcomes. Cancer 2015;121:4250–4257. © 2015 American Cancer Society . Abstract : Patient‐reported resilience is independently associated with health and psychosocial outcomes. Future studies must determine whether resilience screening and interventions can improve survivorship outcomes.